Navigating Tradition and Modernity: A Diachronic Analysis of the Methodological Rupture in Tafsīr al-Taḥrīr wa al-Tanwīr - Habib Abdillah; Abdulaziz Saad Alqahtani; Masruhan, Masruhan; Abideen Opeyemi Yekeen (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
Contrary to its reputation as a unified magnum opus, Tafsīr al-Taḥrīr wa al-Tanwīr is marked by a sharp methodological rupture spanning four decades. By dismantling the prevailing synchronic readings, this study exposes the diachronic evolution of Ibn ‘Āshūr’s exegetical paradigm. Using a qualitative method, a historical approach, and maqāṣidī tafsīr analysis, this study reveals a significant shift from the tradition-based approach (tafsīr bi al-ma’thūr) to a more contextual, reflective, and goal-oriented approach to sharī‘ah (maqāṣid al-sharī‘ah). This methodological shift not only reflects Ibn ‘Āshūr’s intellectual response to the complexities of the times but also confirms the role of his tafsīr as an important work in the development of contemporary tafsīr methodologies that are adaptive, humanistic, and oriented towards problem-solving. The findings of this study confirm that Tafsīr al-Taḥrīr wa al-Tanwīr is not only a significant work of modern exegesis but also an important foundation in the formation of a tafsīr paradigm that addresses the challenges of modernity without abandoning the roots of classical scientific authority.